Optimized Smart Home Temperature Monitoring Using IoT: Pemantauan Suhu Rumah Pintar yang Dioptimalkan Menggunakan IoT - Putra, Dandi Pratama; Ayuni , Shazana Dhiya (Indonesian Journal of Innovation Studies, 2024)
This research aims to monitor residential home temperatures using the Internet of Things (IoT) and Google Sheets. By adopting a Research and Development (R&D) approach, the study designs and tests a temperature monitoring tool with DHT11 sensors, NodeMCU ESP8266, and LCD displays. Data is integrated into Google Sheets for real-time access. The results show improved service efficiency, reducing waiting times to 0.41-2.45 minutes, with fewer waiting customers and lower utilization rates. This system enhances living conditions by providing easy temperature monitoring, recommending future studies to extend data collection periods for comprehensive analysis. Highlight: Efficient Monitoring: Real-time temperature data via Google Sheets. Integrated System: Uses DHT11 sensors and NodeMCU ESP8266. Research Implications: Extend data collection for thorough analysis. Keywoard: Temperature Monitoring, Internet of Things, Google Sheets, DHT11 Sensors, NodeMCU ESP8266